Electro-explosive alloying of VT6 alloy surface by boron carbide powder with the subsequent electron-beam treatment - Romanov D. A.; Raykov S. V.; Gromov V. E.; Ivanov Yu. F. Yuriy Fedorovich (2015, 2015)
Title screen